Social Movement for Rejection of Coastal Reclamation Development in Majene Regency: Social and Environmental Impact Analysis - Tandjung, Muhammad Akbar; Torro, Supriadi; Daniel, Daniel (Pinisi Journal of Social Science, 2023)
The objectives of writing this article are (1) To see the role of social movements in response to the development of Waterfront City/coastal reclamation in Majene Regency. (2) Studying the process of Waterfront City/reclamation development in the coastal area of Majene City. (3) Analyze the implications of Waterfront City/coastal reclamation development on the environment and the socio-economic conditions of fishing communities. The development of Waterfront City in Majene Regency significantly affects the lives of fishing communities and local wisdom. This project threatens their livelihoods that have been dependent on the sea, forcing them to look for alternative jobs due to environmental changes that occur. The method used in this article is descriptive analytical research method. The importance of previous environmental studies is undeniable as it helps identify and mitigate negative impacts, such as coral reef damage that may arise from reclamation. Strict regulations and the application of high standards are vital to ensure the viability of the project. The findings of the environmental assessment related to Waterfront City also indicated potential environmental threats that must be addressed immediately. Fishing communities are fighting in various ways, including direct protests, to protect their environment, cultural heritage and livelihoods from the threats of the project. In the face of these challenges, fishing communities, such as the Alliance to Save Sul-Bar Fishermen and Coastal Areas, continue to work to protect the environment from the negative impacts of Waterfront City development in Majene Regency